2020
DOI: 10.4314/tjpr.v19i5.1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ciprofloxacin activity by incorporating it in solid lipid nanoparticles

Abstract: Purpose: To incorporate ciprofloxacin (CIP) into solid lipid nanoparticles (SLN) in order to enhance its biopharmaceutical properties and antibacterial activity.Methods: A sonication melt-emulsification method was employed for the preparation of CIP-loaded SLN. The composition of the SLN was varied in order to investigate factors such as lipid type and combination ratio, drug to lipid ratio, and surfactant ratio. The produced SLN formulations wereevaluated for their particle size and shape, zeta potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The observed higher cumulative % release with F9, containing a combination of Dynasan 114 and Imwitor 308, is in agreement with the results reported by Alarifi et al [65] for the release of ciprofloxacin from SLN composed of stearic acid/Imwitor 900 or Dynasan 118 combinations. The significant increase in the cumulative CXB% release when using Cremophor EL as a surfactant is in agreement with Kiss et al [66], who concluded that Cremophor EL causes a reduction in the melting point of lipid mixture, resulting in a reduction in their crystallinity index.…”
Section: Discussionsupporting
confidence: 92%
“…The observed higher cumulative % release with F9, containing a combination of Dynasan 114 and Imwitor 308, is in agreement with the results reported by Alarifi et al [65] for the release of ciprofloxacin from SLN composed of stearic acid/Imwitor 900 or Dynasan 118 combinations. The significant increase in the cumulative CXB% release when using Cremophor EL as a surfactant is in agreement with Kiss et al [66], who concluded that Cremophor EL causes a reduction in the melting point of lipid mixture, resulting in a reduction in their crystallinity index.…”
Section: Discussionsupporting
confidence: 92%
“…The lipids used in the ultrasonication and high-speed homogenization methods include glyceryl behenate and tri-behenate (Compritol), glycerol monostearate (GMS), tristearin glyceride, and stearic acid [ 21 ]. At the same time, the surfactants that can be used are Poloxamer 188, Lecithin, and Tween [ 79 , 87 ]. The synthesis of SLNs using the ultrasonication method begins by dissolving the active compound to be encapsulated with melted lipid, and then the mixture is heated to 10 °C above the lipid melting point.…”
Section: Fabrication Methods For Slnsmentioning
confidence: 99%
“…The synthesis of SLNs using the ultrasonication method begins by dissolving the active compound to be encapsulated with melted lipid, and then the mixture is heated to 10 °C above the lipid melting point. The mixture of lipids and active compounds is then mixed into a liquid phase containing preheated surfactants and cosurfactants; the mixture is then heated to the same temperature as before and stirred slowly until a pre-emulsion is formed [ 52 , 87 ].…”
Section: Fabrication Methods For Slnsmentioning
confidence: 99%
“…The outcomes of the pharmacodynamic investigation show that both topical and oral Pi have a suitable response compared to for example oral chloroquine suspension. Alarifi et al [ 156 ] designed formulations of ciprofloxacin (CIP) into SLNs as a means to improve its biopharmaceutical and biochemical properties and its anti-inflammatory properties. The results of the evaluation showed that encapsulation of CIP in SLNs increased its antimicrobial and anti-inflammatory activities in vitro which could significantly improve a treatment by reducing dose-dependent side effects and increasing the range of protective activities.…”
Section: Nanomaterials For the Treatment Of Inflammatory Arthritismentioning
confidence: 99%